First Field-Based Evidence That the Seagrass-Lucinid Mutualism Can Mitigate Sulfide Stress in Seagrasses - van der Geest, Matthijs; van der Heide, Tjisse; Holmer, Marianne; de Wit, Rutger (Frontiers in Marine Science, 2020)
Seagrass meadows form vital ecological components of coastal zones worldwide, but are rapidly declining. Large-scale seagrass diebacks have been related to accumulation of toxic sulfide in the sediment, a phenomenon predicted to occur more frequently in the near future due to ongoing global warming and increasing organic loading of coastal systems worldwide. Recently, a facultative mutualism between seagrasses and lucinid bivalves with endosymbiotic sulfide-consuming gill bacteria was discovered that may prevent toxic sulfide accumulation in seagrass sediments. Yet, direct field-based evidence for the importance of this mutualism in alleviating sulfide stress in seagrasses is currently lacking, as well as how its role may change when sediment sulfide levels increase due to environmental change. Here, we investigated the sulfide detoxification function of this seagrass-lucinid mutualism and its resilience to organic-loading induced sulfide stress in a temperate lagoon system (Thau lagoon, France), using a correlative field survey and a full factorial field experiment. The field survey revealed a strong positive correlation between seagrass above-ground biomass and lucinid densities, and pore water sulfide concentrations close to zero at all sites. Furthermore, the field experiment revealed that addition of organic matter (starch mixed with sucrose) increased sedimentary sulfide intrusion into seagrass (Zostera noltei) leaves (a proxy for sulfide stress), while experimentally enhanced lucinid densities reduced sulfide intrusion, regardless of addition of organic matter. Moreover, addition of organic matter reduced seagrass rhizome biomass and increased pore water sulfide levels, lucinid tissue sulfur content, lucinid condition (expressed as flesh/shell dry weight ratio), and total lucinid biomass, while enhancement of lucinid densities reduced lucinid condition. These results provide the first field-based evidence that lucinid bivalves and their sulfide-oxidizing gill symbionts mitigate sulfide stress in seagrasses, and suggests that the dependence of seagrass on this seagrass-lucinid mutualism will increase under conditions of enhanced sediment sulfide production, as predicted for the near future. Therefore, we suggest that awareness of the ecological importance of the seagrass-lucinid mutualism may be instrumental for designing new measures for improving long-term restoration success and seagrass resilience to global change.